Zooplankton_Data_Compilation_Arctic_Ocean_Part_2_Eastern_Hemisphere_White_Sea_Kara_Sea_Laptev_Sea_1951-2007 - NSF Arctic Data Center (Arctic Data Center, 2014)
This dataset is a compilation of numerous individual datasets presenting abundance and/or biomass data for zooplankton communities in the Arctic Ocean and including the White Sea, Kara Sea, East Siberian Sea and Laptev Sea from 1951-2007. This data originates from various investigators and institutions either provided by the investigator or having been rescued from the printed literature. Every effort has been made to standardize the data in terms of currently accepted taxonomy, life stage and abundance and biomass units. HOWEVER, IT IS IMPOSSIBLE TO FULLY COMPENSATE FOR DIFFERENCES IN SAMPLING METHODS (MESH SIZE, TOW SPEED, SAMPLING DEPTH, BIOMASS CONVERSIONS), TAXONOMIC RESOLUTION AND TAXONOMIC SKILL. THIS DATA CANNOT BE USED AS IS WITHOUT UNDERSTANDING THE ASSOCIATED BIASES, WHICH CAN VARY WIDELY FROM SPECIES TO SPECIES, WITH PRONOUNCED IMPACTS ON BIODIVERSITY AND REALATIVE COMMUNITY COMPOSITION. Database Headers. Data_Base_Reference_ID- A numerical reference to the row number of the database. Bibliographic_Citation- The citation, author and or scientific paper from which individual data are referenced. Please refer to these individual citations for a complete description of sampling and taxonomic protocols unique to the individual dataset. Date_Last_Modified. The date of the last modification of the individual datasets. MM/DD/YYYY. Catalog_Number. The catalog number corresponding to each entry in an individual dataset. Date_Collected. The date when the sampling event occurred. MM/DD/YYYY. Month_Collected. The month of the year in which the sampling event occurred. 1-12; January-December. Day_Collected. The day of the month on which the sampling event occurred. 1-31. Year_Collected. The year in which the sampling event occurred. YYYY. Time_Collected. The time of day that the sampling event occurred: 0:00-23:59. Start_Time_of_Day. The time of day that the sampling event was initiated: 0:00-23:59. End_Time_of_Day. The time of day that the sampling event was completed: 0:00-23:59. Not valid for all datasets. Time Zone: The time zone employed for documenting the sampling event. Not valid for all datasets. Platform. The vessel or sampling location from which the sampling event occurred. Not available for all datasets. CruiseID. The code or name given to the specific cruise track. StationID. The original code or name given to the station location. DecimalLatitude. The latitude of the sampling location in decimal degrees. DecimalLongitude. The longitude of the sampling location in decimal degrees. ContinentOcean. The Ocean and/or continent associated with the sampling location. Waterbody. The regional waterbody of the sampling location within the specified Ocean Locality. The specific locality of the sampling location within the specified waterbody Basis_of_Record. The type of specimen used to acquire the datapoing. In the vast majority of cases the datapoint was obtained from preserved samples. Collecting_Gear. Specifics regarding the sampling gear type and dimensions for each individual dataset. Mesh_Size. The pore size of the mesh that was used to collect each sample. Pore size has been standardized to micrometers (um). Minimum_Depth_In_Meters. The minimum depth from which the collecting gear was deployed. All data has been standardized to meters (m). Maximum_Depth_in_Meters. The maximum depth to which the sampling gear was deployed. All data has been standardized to meters (m). Sonic_Depth_in_Meters. The depth of the water column at the sampling location as measured by vessel acoustics of soundings. All data has been standardized to meters (m). Scientific_Name. The scientific name of the identified organism. Identified organisms are listed to the lowest taxonomic resolution available from the original description. For instance, if the generic name is listed and the species names are not described, this could represent one or more species. All names have been updated to reflect taxonomic description based on the World Register of Marine Species www.marinespecies.org as of September 2014. Original_Name. The description of the identified organism as described by the original dataset or paper. Taxonomic names were changed to reflect standardized taxonomic hierarchy. World Register of Marine Species. www.marinespecies.org. ie. Unidentified copepods would be standardized to Copepoda. Notes. Any notes associated with the original description of the identified organism corresponding to taxonomy or condition of the animal. Accepted_ Scientific_Name. The accepted scientific name of the identified organism generated by the World Register of Marine Species. www.marinespecies.org as of September 2014. Accepted_ APHIA_No. The current and accepted APHIA identification number that corresponds to the updated taxonomy of the identified organism generated by the World Register of Marine Species. www.marinespecies.org Accepted_TSN. The current and accepted Taxa Specific Number that corresponds to the updated taxonomy of the identified organism generated by th eWorld Register of Marine Species. www.marinespecies.org. Life_Stage. The lifestage of the identified organism. All lifestages are written in full text with the exception of CI-CV referring to copepodite stages 1. Sex. The sex of the identified organism where determined. Size. When described, the size of the identified organism. Size is not standardized to any cosistent unit Abundance/m2. The abundance of the identified organisms per square meter of the entire water column (#/m2). Not valid for all individual datasets. Unit of Measurement. The measurement units of the previous column. Sample size. When applicable, the volume of water sampled during the sampling event in cubic meters (m3). Abundance/m3. The abundance of the identified organism in terms of #/m3. When abundance was described in unit of #/m2, these values were divided by the sample depth to obtain #/m3. Zero abundances are not recorded Biomass. When applicable, the biomass of the identified organism. Units have not been consistently standardized. In most cases unit are mg/m3. Please refer to the unit of measurement column for description of units. Collector. The persons or institution responsible for collection the sample. Identified_By. The person responsible for identification of the given organism.